2016
DOI: 10.2967/jnumed.115.171371
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Targeted Radioimmunotherapy for the Treatment of Glioblastoma

Abstract: Rationale Glioblastoma is characterized by an aggressive and aberrant vascular network that promotes tumor progression and hinders effective treatment; the median survival is 16 months despite standard-of-care therapies. There is a need to improve therapeutic options for this disease. We hypothesized that antibody targeting of the vascular endothelium (VE) of glioblastoma with cytotoxic short-range, high-energy alpha particles would be an effective therapeutic approach. Methods E4G10, an antibody directed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The RCAS-vector carries the tumor-driver human Platelet-derived growth factor (PDGF) B. Tumor was induced by stereotactic intracranial surgery as previously described (13). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RCAS-vector carries the tumor-driver human Platelet-derived growth factor (PDGF) B. Tumor was induced by stereotactic intracranial surgery as previously described (13). …”
Section: Methodsmentioning
confidence: 99%
“…225 Ac-E4G10 as an alternative anti-vascular approach and our preclinical studies in transgenic glioblastoma mice showed therapeutic activity and increased survival significantly as monotherapy (13). We imaged the microenvironment architecture and function in remodeled tumor resulting from α-particle irradiation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…2). Because of the particle range, this cross-fire effect is thought to be higher with b-emitters, but recent studies showing a-particles to have a significant therapeutic effect on large tumors question this concept (6)(7)(8). In addition to direct effects, indirect radiation effects have been observed.…”
Section: α-Emitting Isotope Radiochemistrymentioning
confidence: 99%
“…Although studies of biologic effects from a-particles would gain from a dosimetry more detailed than mean absorbed dose to whole organs in most cases, we chose to evaluate the antitumor effects with respect to mean absorbed dose to whole tumor. Using targeted a-therapy on solid tumors, antitumor effects may arise not only from irradiation of tumor cells but also from other targets, such as intratumoral vasculature (25)(26)(27)39,40). High-resolution a-camera imaging of the same tumor model as used here (21) showed clearly heterogeneous intratumoral activity distributions of up to 7 h after injection.…”
Section: Discussionmentioning
confidence: 99%